Cold water = L' eau froide - Assayas, Olivier 1955-; Lenoir, Denis 1949-; Clavel, Françoise ca. 20. Jh; Ledoyen, Virginie 1976-; Fouquet, Cyprien; Szabó, László 1936- (<<The>> Criterion Collection, 2018)
"[...] Drawing from his own youthful experiences, Assayas revisits the outskirts of Paris in the early 1970s, telling the story of teenage lovers Gilles (Cyprien Fouquet) and Christine (Virginie Ledoyen), whose rebellions against family and society threaten to tear them apart. The visceral realism of the movie’s narrative and the near experimentalism of its camera work come together effortlessly thanks in part to a rock soundtrack that vividly evokes the period. "Cold Water", whose centerpiece is one of the most memorable party sequences ever committed to film, is a heartbreaking immersion in the emotional tumult of being young." [criterion.com]
Original: Frankreich 1994
Bildformat 1.66:1
Director-approved special edition features: new 4K digital restoration, supervised by director Olivier Assayas ; new interview with Assayas ; new interview with cinematographer Denis Lenoir ; excerpt from a 1994 French television program on the film featuring Assayas and actors Virginie Ledoyen and Cyprien Fouquet ; new English subtitle translation ; plus an essay by critic Girish Shambu
Keywords: Film; DVD-Video